855. Persistence on F/TAF versus F/TDF for HIV Pre-Exposure Prophylaxis: A Real-World Evidence Analysis in the United States. (4th December 2021) - Tao, Li; Shvachko, Valentina; Das, Moupali; Carter, Christoph C; Baeten, Jared; Magnuson, David
Abstract: Background: Persistence to preexposure prophylaxis (PrEP) is an important determinant of its efficacy, but evidence on real-world persistence is lacking. This study assesses adherence to F/TDF and F/TAF for PrEP both in terms of discontinuation and re-initiation patterns. Methods: We identified HIV-negative individuals in the United States who initiated F/TDF or F/TAF for PrEP between October 2019 and December 2020 from a de-identified prescription claims database; users taking generic F/TDF were excluded. Non-persistence was defined as a prescription fill gap of >30 days; discontinuation included switch from F/TDF to F/TAF or F/TAF to F/TDF. We used survival analyses to estimate persistence, Cox regressions to compare the hazard ratios (HR) of discontinuation, and logistic regression to compare the odds ratios of re-initiation after discontinuation. Results: Among F/TAF users (N=82, 402) median age at PrEP initiation was 35 years (interquartile range [IQR] 28−47) and median PrEP persistence was 4 months (IQR 1.8-8.9), compared to 31 years (IQR 25−40) and 2 months (IQR 1.0-3.8) for F/TDF users (N=48, 501). PrEP persistence at 60 and 90 days was higher among F/TAF users than F/TDF users (Figure). F/TDF users were 2.5 times more likely to discontinue than F/TAF users, with more marked differences in older users than that in younger users ( p for interaction between discontinuation and age group < 0.01, Table). We also observed a higher rate of discontinuation of F/TDF versus F/TAF if PrEP was prescribed by internal medicine or infectious disease physicians than by family medicine physicians (data not shown). After discontinuation, F/TAF users were 1.7 times more likely than F/TDF users to re-initiate PrEP; the association was not different by age. Persistence rates of F/TAF and F/TDF for PrEP by time of PrEP initiation Hazard ratios (HR) and corresponding 95% confidence intervals (CI) of non-persistence and odds ratios (OR) of re-initiation after discontinuation for users of F/TAF and F/TDF for PrEP in the US, Oct 2019 – Dec 2020 Conclusion: In this real-world analysis, the F/TAF for PrEP regimen was associated with higher persistence and re-initiation than F/TDF for PrEP. These findings underscore the dynamic nature of PrEP utilization in the real-world and the importance of interventions aimed at improving PrEP persistence and re-initiation in people who would benefit from PrEP. Disclosures: Li Tao, MD, PhD, Gilead Sciences Inc (Employee, Shareholder) Valentina Shvachko, MS, Gilead Sciences Inc (Employee, Shareholder) Moupali Das, MD, Gilead Sciences Inc. (Employee, Shareholder) Christoph C. Carter, MD, Gilead Sciences Inc. (Employee, Shareholder) Jared Baeten, MD, PHD, Gilead Sciences Inc. (Employee, Shareholder) David Magnuson, PharmD, Gilead Sciences Inc (Employee, Shareholder)